Produksi Susu Kambing Peranakan Etawah Sebagai Respon Pemberian Probiotik dan Mineral Seng dalam Ransum : Etawah Crossbreed Goat Milk Production as a Response to the Providing Probiotics and Zinc Minerals in the Feed - Adriani, Adriani; Darlis, Darlis; Andayani, Jul; Novianti, Sri (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
The productivity of Etawah crossbreed goats in producing milk and meat is not yet optimal. Milk production can be increased by providing zinc and probiotics. Zinc plays a role in helping the digestive process and increasing growth. Meanwhile, probiotics can increase digestibility and milk production. This research aims to determine the effect of providing the mineral zinc (Zn) and probiotics on the milk production of Etawah Crosbreed goats. This study used 12 first and second lactation Etawah crossbreed goats. A randomized block design was used with three treatments and four replications, namely P0 = control (70% forage + 30% concentrate), P1 = P0 + 2% probiotics, P2 = P1 + Zn 60 g/kg BW. The parameters observed were feed dry matter consumption, protein, fat and crude fiber, milk production, milk quality (specific gravity, protein, fat, lactose and dry matter). The research results showed that probiotics and Zn had no effect on consumption of diet dry matter, crude protein, diet fat (P.0.05). Probiotic and Zn treatment can increase milk production (P<0.05), where P2 is higher than P1 and P0 and P1 are higher than P0. However, it did not affect the quality of milk, namely protein, fat, lactose and dry matter of Etawah Crosbreed goats (P>0.05), except for the specific gravity of the milk. The research conclusion was that the provision of probiotics and Zn minerals did not affect feed consumption and milk quality, but increased milk production.